Mostrando os estados contrários da alma humana: um estudo das canções de inocência e de experiência, de William Blake - Oliveira, Leandro Cardoso de (2015)
William Blake was a painter, poet and printmaker. The author demonstrated a large experimentation in the production of his art, developing his own method of printing and publishing. Such method made possible the creation of the so called illuminated books, support in which was published most of his composite art, which combines poetry and painting in an inseparable way. This dissertation aims to examine the states of "Innocence" and of "Experience" in the illuminated books Songs of Innocence (1789), Songs of Experience (1794) and Songs of Innocence and of Experience - Shewing the Two Contrary States of the Human Soul (1794 ). Usually, the Blake's "Innocence state", in the text and in the visual compositions, is associated with idealized existence, childhood figures and fertile nature. "Experience", on the other hand, presents urban scenes or arid nature, adult images and a different perspective about life, without the characteristic idealization of "Innocence". However, although the titles of the volumes indicate which compositions would be of "Innocence" and what would be of Experience", the compositions have evidences that perhaps these states are not clearly defined or contrary, as the subtitle of the agglutinated edition indicates. Examples of it, besides adult figures on the Innocence book and childhood images on the Experience , are compositions that appear in both Songs of Innocence and Songs of Experience, depending on the copy. Considering the switchable aspect of this collection of poems and the reallocations made by Blake in the several copies of the books, it will be observed what is the elements that fundaments the states of "Innocence" and of "Experience" on the three books of Songs.